The transition of continuous pedagogical education system to the development cluster model - Y.V., Ponomarenko; Y. S., Kozybayev; V. P., Bondarenko; L. A., Larchenkova (Opción, 2019)
This article aims to develop a methodology and theory of the transition of the system of continuous pedagogical education in the cluster model of development. To achieve the goal, theoretical research methods were used - information monitoring, comparative analysis, synthesis, systematization, hypothesis formulation. As a result, a competent specialist, by virtue of systematic professional development, creates and implements innovations, and is also responsible for the made decisions, both in personal and professional spheres. In conclusion, a scientific substantiation of the fact that the cluster approach has a positive effect on the formation of students' competencies.